Description of nymphs and female subimago of Sparsorythus multilabeculatus Sroka & Soldán, 2008 (Ephemeroptera: Tricorythidae) associated with male imago based on DNA sequence data - Piraonapicha, Kanyakorn; Sangpradub, Narumon (Zootaxa, 2019)
Sparsorythus is a genus of Tricorythidae from the Oriental Region. Sparsorythus multilabeculatus Sroka & Soldán, 2008 was described based on a male imago from Vietnam. Unknown nymphs and female subimagines of Sparsorythus and male imagines of S. multilabeculatus were collected from Thap Lan National Park, Khon Buri District, Nakhon Ratchasima Province, Thailand. Nymphs and female subimagines of Sparsorythus were associated with male imagines of S. multilabeculatus by analyzing sequences from the DNA barcoding region of the mitochrondrial gene cytochrome oxidase I. Phylogenetic analysis based on Maximum Likelihood indicated that all unknown specimens are conspecific with male imagines of S. multilabeculatus (bootstrap 100% and genetic distance 0–0.004). Male and female nymphs, female subimago and egg are described for the first time. Nymphs each bear a medial emargination on the hypopharynx, one bristle-like process at the base of the left prostheca, and a bifurcate rudimentary gill on abdominal segment VII. The male usually has smudges and light blotches on its forewings; the penis extends to the basal segment of the forceps and reaches to approximately 1/3 of the second segment of the forceps. Forewings of the female subimago have dark colour over more than half of the basal area, and the distal portion of each wing is translucent. The egg has a rounded pole; the polar cap covers approximately 1/4 of the surface; and the surface is covered with hexagonal structures.